Evaluating masure the psychologis't forces for standardized questioner for handball players - Turky , Wafaa (Journal of Physical Education, 2010)
The first chapter contains the introduction with the importance of sport psychologist forces which impose the players that clemand study this change to know the level of these forces and treat them. Also aim of this research to evaluating the standard of the psychologist forces for. Stadarized questioner for hand ball players represented the Iraq leaque. The second chapter has the study of psychologist forces for hand ball players and the sources of these forces by using the survey style and the sample of building the scale for hand ball players of super level in Iraq which involves (171) players form (13) clubs. The survey procedures were to practice the style which involve (27) step divided loy six aspects and they were corrected the style with four substitutions. The fourth chapter was evaluating the procedures. It was found of through groups . the results were to accept three from six factors and the lost practical procedures were evaluating were to derine the masure standend by using the degree of (T. score Norm). Also form the results of this research were to accept three factors and they were colled and the number of standered were (14) steps